Income elasticity of gasoline demand: A meta analysis - Tomáš Havránek; Kokeš Ondřej (Charles University in Prague, Institute of Economic Studies (IES), 2013)
In this paper we quantitatively synthesize empirical estimates of the income elasticity of gasoline demand reported in previous studies. The studies cover many countries and report a mean elasticity of 0.28 for the short run and 0.66 for the long run. We show, however, that these mean estimates are biased upwards because of publication bias - the tendency to suppress negative and insignificant estimates of the elasticity. Using mixed-effects multilevel meta-regression we filter out publication bias from the literature. Our results suggest that the income elasticity of gasoline demand is smaller than commonly thought: the corrected estimate is 0.1 for the short run and 0.46 for the long run.
Keywords: C83; Q41; 330; gasoline; income elasticity; publication bias; meta-analysis